STUDY OF THERMAL AND HYDROLYTIC DENATURATION OF CASEIN (αS1) USING DIFFERENTIAL SCANNING CALORIMETRY (DSC) - Z. Farooq (Journal of Animal and Plant Sciences, 2019)
Among various casein variants, α-S1 has been identified as potential allergen for the sensitive individuals. In this study various thermal and hydrolytic techniques have been employed to denature casein for its extended use as functional ingredient especially to manage allergy. This study aims to denature casein (αS1) for characterization as functional ingredient in various food and nutraceutical formulations.  Casein was denatured using standard thermal (dry, wet and microwave heat) and hydrolytic (using various enzymes) techniques. Denatured casein was characterized using Differential Scanning calorimetry (DSC). Native casein showed thermal transition (∆Hd) at 0.079 J/g corresponding to the denaturation temperature 103.7570C. Denatured casein showed new epitopes according to various degrees of denaturation as reflected by variable enthalpies (∆Hd) corresponding to specific denaturation temperatures. Dry heat treatment for 60 minutes and wet for 45 minutes showed significant thermal denaturation of casein giving 11.05 and 193.10 J/g enthalpies corresponding to 109.775 and 122.472 0C and 0.002 and 0.002 J/g enthalpies corresponding to 116.425 and 120.173 0C denaturation temperatures respectively. Similarly, hydrolytic denaturation of casein by various enzymes showed variable enthalpies (∆Hd). Casein showed new epitope formation due to which it can be used as diversified functional ingredient.
Keywords: Casein; hydrolysis; thermal denaturation; DSC